Adverse childhood experiences, childhood relationships and associated substance use and mental health in young Europeans - Hughes, Karen; Bellis, Mark A.; Sethi, Dinesh; Andrew, Rachel; Yon, Yongjie; Wood, Sara; Ford, Kat; Baban, Adriana; Boderscova, Larisa; Kachaeva, Margarita; Makaruk, Katarzyna; Markovic, Marija; et al. (Oxford University Press, 2019)
Adverse childhood experiences (ACEs) can increase risks of health-harming behaviours and poor health throughout life. While increases in risk may be affected by resilience resources such as supportive childhood relationships, to date few studies have explored these effects.
Keywords: alcohol abuse; ethanol; smoking; alcohol drinking; child; mental disorders; mental health; suicide attempt; stress; drug usage; substance use disorders; health outcomes; young adult; adverse childhood experiences